Komunikasi Simbolik Penonaktif Centang Biru di WhatsApp (Studi Kualitatif pada pengguna yang menon-aktifkan centang biru di WhatsApp) - Rizky Ramdani; Veny Purba; Riefky Krisnayana (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study aims to understand users’ interpretation of the absence of the blue tick feature (read receipts) on WhatsApp in interpersonal communication. This phenomenon is no longer perceived merely as a technical setting, but also as a form of symbolic communication that influences the dynamics of digital interaction. This study employed a qualitative method with a phenomenological approach to explore participants lived experiences in depth. The analytical framework used was the Symbolic Interaction Theory developed by George Herbert Mead and Herbert Blumer, focusing on its three main premises: meaning, interaction, and thought. Data were collected through semi-structured in-depth interviews, observation, and documentation involving six Communication Science students at Langlangbuana University who actively disabled the feature. The findings indicate that the absence of read receipts is interpreted as a form of privacy regulation and a comfort instrument to protect users from the pressure of instant communication expectations. In terms of interaction, this action functions as a form of social negotiation to reduce pressure for immediate message replies, although it often triggers complaints from surrounding individuals who expect communication transparency. Internally, the absence of reading indicators creates a miscommunication phenomenon in the form of “replying to messages mentally,” while also fostering a sense of empathetic consensus among fellow users who disable the feature. In conclusion, the absence of blue ticks represents a conscious strategy employed by users to manage time autonomy, privacy, and personal boundaries in cyberspace.